Effect of an extruded animal protein‐free diet on fecal microbiota of dogs with food‐responsive enteropathy. (23rd October 2018) - Bresciani, Francesca; Minamoto, Yasushi; Suchodolski, Jan S.; Galiazzo, Giorgia; Vecchiato, Carla G.; Pinna, Carlo; Biagi, Giacomo; Pietra, Marco
Abstract : Background: Dietary interventions are thought to modify gut microbial communities in healthy individuals. In dogs with chronic enteropathies, resolution of dysbiosis, along with remission of clinical signs, is expected with treatment. Hypothesis/Objective: To evaluate changes in the fecal microbiota in dogs with food‐responsive chronic enteropathy (FRE) and in healthy control (HC) dogs before and after an elimination dietary trial with an animal protein‐free diet (APFD). Animals: Dogs with FRE (n = 10) and HC (n = 14). Methods: Dogs were fed the APFD for 60 days. Fecal microbiota was analyzed by Illumina 16S rRNA sequencing and quantitative polymerase chain reaction (PCR). Results: A significantly lower bacterial alpha‐diversity was observed in dogs with FRE compared with HC dogs at baseline, and compared with FRE dogs after the trial. Distinct microbial communities were observed in dogs with FRE at baseline compared with HC dogs at baseline and compared with dogs with FRE after the trial. Microbial communities still were different in FRE dogs after the trial compared with HC dogs at baseline. In HC dogs, the fecal microbiota did not show a significant modification after administration of the APFD. Conclusion and Clinical Importance: Our results suggest that, in FRE dogs, treatment with the APFD led to a partial recovery of the fecal microbiota by significantly increasing microbiota richness, which was significantly closer to a healthy microbiota after the treatment. In contrast, no changes were detected in the fecal microbiota of HC dogs fed the same APFD.